Legalitas Aborsi Akibat Pemerkosaan Ditinjau Dari Prespektif Korban Dan Hak Asasi Manusia - Junisa Putri Salsabila; Winda Fitri (Widya Yuridika, 2022)
Abortion is an act of abortion of content by using it without forcibly removing it due to certain circumstances.  If viewed from an Islamic perspective, abortion is not permitted under Islamic law, but in Government Regulation (PP) No.  61 of 2014.  Abortion due to legal consequences is allowed if it has not reached the age of 40 days.  The existence of different views on the law established by the state with applicable Islamic law raises the pros and cons of implementing the legalization of abortion in Indonesia.  This study was conducted to find out how the legalization of abortion is based on considerations from the perspective of victims and human rights and how the views of Islamic law are related to abortion due to rape.  This study will focus on the legalization of abortion that occurs in cheating victims with the view of Islamic law which sees that all murders are sins.  This study uses an approach with a literature study method to obtain related data from reliable sources with continuous data management.  Abortion is carried out as a result of love in the view of Islamic law, in principle is not allowed because harm cannot be reciprocated by harm.  Although state law has legalized abortion for victims of sacrifice because the majority of religion in Indonesia is Islam.  But at the core of its application, any abortion carried out without medical conditions is not permitted.